Booth Tarkington papers - Tarkington, Booth, 1869-1946.
Manuscript page from Tarkington's The Conquest of Canaan (1905); ALS (1905 June 27) from his wife, Louisa Fletcher Tarkington, regarding his published works; and a reproduction of James Montgomery Flagg's drawing of Tarkington signed by Tarkington (undated).
Author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Flagg, James Montgomery, -- 1877-1960.; Tarkington, Louisa Fletcher -- Correspondence; American literature; Authors